Effects of postruminal amino acid supplementation on protein deposition and the mammalian target of rapamycin signaling pathway in growing steers - Pearl, Kimberly Anne (Kansas State University, 2019)
Two experiments were conducted to determine effects of postruminal amino acid (AA) supplementation on protein deposition and signaling of the mammalian target of rapamycin (mTOR) pathway. For both experiments, 7 ruminally cannulated Holstein steers (172.7 ± 3.7 and 201.7 ± 3.8 kg initial BW in Exp. 1 and 2, respectively) were utilized in 6  6 Latin square designs with 7 d periods. A basal AA solution containing all essential AA, with the exception of lysine, were provided to all steers in each study in order to meet growth requirements, while making lysine the only limiting AA. Steers were fed 2.8 kg/d of a pelleted soyhull diet designed to be low in ruminally undegradable protein. Glucose was infused abomasally and volatile fatty acids were infused ruminally to prevent energy from being limiting. Steers were housed in metabolism crates to obtain total collection of both urine and feces. Blood and muscle biopsies of the longissimus lumborum were collected on the last day of each period. In experiment 1, treatments consisted of 2 levels of lysine (0 or 6 g/d) and 3 levels of leucine (0, 15, or 30 g/d) infused abomasally. Nitrogen retention increased with supplemental lysine. Leucine linearly decreased plasma concentrations of total AA. Plasma urea N (PUN) decreased with supplemental lysine. Total, phosphorylated, and the percent phosphorylated Akt were unaffected by treatments. The percentage of 4E-BP1 phosphorylated decreased linearly when leucine was supplemented. A tendency for a lysine x quadratic leucine effect was observed for the ratio of phosphorylated RPS6²⁴⁰/²⁴⁴ in which the intermediate level of leucine led to a decrease in the percent of RPS6²⁴⁰/²⁴⁴ phosphorylated when no lysine was supplied but increased when 6 g lysine/d was supplied. No differences were observed in the abundance of total, phosphorylated, or percent phosphorylated mTOR or in total abundance of E3 ubiquitin ligase proteins, MuRF1 or MAFbx. Experiment 2 was conducted similarly as experiment 1. Treatments consisted of 2 levels of lysine (0 or 6 g/d) and 3 mixtures of supplemental essential AA [none (control), 103 g/d essential AA (EAA), or EAA plus 30 g/d leucine (EL)] abomasally infused. Supplementation with essential AA, with or without leucine, increased the percentage of RPS6 phosphorylated, with a greater increase when leucine was included as part of the supplement. A lysine x (control vs. EAA+EL) interaction was observed for N retention in which the EAA and EL treatments did not improve N retention when no lysine was supplemented, but they increased it when 6 g lysine/d was provided. PUN increased above control when EAA or EL was provided, but PUN decreased when lysine was supplied. Supplementation of EAA or EL increased plasma total AA concentrations, but EL led to lower total plasma AA than EAA; however, concentrations were greater for EL than for control. In summary, leucine supplementation alone did not yield effects on whole-body protein deposition or on regulatory factors known to affect muscle protein synthesis, whereas a mixture of excess essential AA improved both lysine utilization and phosphorylation of RPS6²⁴⁰/²⁴⁴. These studies demonstrate the effects of essential AA, both limiting and nonlimiting, on protein deposition in growing cattle.
Keywords: Leucine; Amino acids; Steer; Protein deposition; mTOR